Improving the quality of therapeutic communication in patients through infrared devices at Puskesmas Kraton Yogyakarta - Adhianty Nurjanah; Iswanto Iswanto (Community Empowerment, 2023)
The growth of the science and technology has a positive effect. One of them is infrared, which is employed as a tool for therapeutic purposes. Based on observations at the Puskesmas Kraton Yogyakarta, it is known that there is no new android-based infrared therapy device and that the quality of therapeutic communication with patients is still insufficient. In order to improve the quality of care provided to patients, this activity aims to increase the value of health professionals' understanding of the significance of therapeutic communication and cutting-edge therapeutic tools. The methodology uses grants for Android-based Infrared devices at the Puskesmas Kraton Yogyakarta as well as training and support for therapists' therapeutic communication. As a result of community empowerment, therapists' capacity to communicate therapeutically with patients has increased by up to 87%, and the effectiveness of therapy assisted by infrared devices has increased by up to 85%.